Genome-wide identification of bone metastasis-related microRNAs in lung adenocarcinoma by high-throughput sequencing. - Lin Xie; Zuozhang Yang; Guoqi Li; Lida Shen; Xudong Xiang; Xuefeng Liu; Da Xu; Lei Xu; Yanjin Chen; Zhao Tian; Xin Chen (PLoS ONE, 2013)
BACKGROUND:MicroRNAs (miRNAs) are a class of small noncoding RNAs that regulate gene expression at the post-transcriptional level. They participate in a wide variety of biological processes, including apoptosis, proliferation and metastasis. The aberrant expression of miRNAs has been found to play an important role in many cancers. RESULTS:To understand the roles of miRNAs in the bone metastasis of lung adenocarcinoma, we constructed two small RNA libraries from blood of lung adenocarcinoma patients with and without bone metastasis. High-throughput sequencing combined with differential expression analysis identified that 7 microRNAs were down-regulated and 21 microRNAs were up-regulated in lung adenocarcinoma with bone metastasis. A total of 797 target genes of the differentially expressed microRNAs were identified using a bioinformatics approach. Functional annotation analysis indicated that a number of pathways might be involved in bone metastasis, survival of the primary origin and metastatic angiogenesis of lung adenocarcinoma. These include the MAPK, Wnt, and NF-kappaB signaling pathways, as well as pathways involving the matrix metalloproteinase, cytoskeletal protein and angiogenesis factors. CONCLUSIONS:This study provides some insights into the molecular mechanisms that underlie lung adenocarcinoma development, thereby aiding the diagnosis and treatment of the disease.